Poverty and inequality in Latin America: the impact of adjustment and recovery in the 1980s - Morley, Samuel (Johns Hopkins University Press, 1995)
[This book] uses recently available household surveys for the majority of Latin American countries to establish what happened to poverty and inequality over the decade and to isolate the main factors that determined the changes observed